Pelatihan Statistik Menggunakan Aplikasi SPSS untuk Peningkatan Keterampilan Karya Ilmiah Guru Sekolah Dasar di Kabupaten Bangkalan - zainal Arifin; Rendra Sakbana Kusuma (IKIP PGRI Bojonegoro, 2021)
The problem faced by elementary school teachers in Bangkalan district is the lack of teacher productivity in producing scientific papers. Teachers are unproductive in making scientific papers due to a lack of understanding of research methodologies and mastery of SPSS applications that can help processing data with statistical techniques, but making research is very important to fulfill the obligations of teachers as professional educators, especially in increasing ranks. This is what underlies the implementation of the implementation of community service activities packaged in the form of statistical training which includes activities: 1) identification of problems 2) Flow of Training Activities 3) Program preparation 4) Program training. The result of this service is that the participants understand the concept of making scientific works and are skilled in carrying out statistical analysis to improve the quality of the profession and develop the quantity of scientific works. Simple research that can produce scientific articles. he implementation of service for elementary school teachers in Bangkalan Regency can be concluded to be successful until the training stage in analyzing research data using the SPSS application and being able to read the output results from the use of the SPSS application. Keywords: Training, SPSS Application, Statistics ABSTRAKPermasalahan yang dihadapi oleh guru SD di kabupaten Bangkalan adalah kurangnya produktifitas guru dalam menghasilkan karya ilmiah. Tidak produktifnya guru membuat karya ilmiah disebabkan kurangnya pemahaman tentang metodologi penelitian dan penguasaan aplikasi SPSS yang dapat membantu mengolah data penelitian dengan menggunakan teknik statistik, padahal membuat penelitian sangat penting untuk memenuhi kewajiban guru sebagai tenaga pendidik profesional utamanya dalam mengajukan kenaikan pangkat. Hal inilah yang mendasari pelaksanaan Pelaksanaan kegiatan abdimas dikemas dalam bentuk pelatihan statistik yang meliputi kegiatan: 1) identifikasi masalah 2) Alur Kegiatan Pelatihan 3) Persiapan Program 4) Pelatihan Program. Hasil dari pengabdian ini adalah peserta memahami konsep pembuatan karya ilmiah dan trampil dalam melakukan analisis statistik untuk pengembangan profesi dan pentingnya peningkatan kualitas maupun kuantitas pengembangan karya ilmiah. Penelitian sederhana yang dapat menghasilkan artikel ilmiah. Pelaksanaan pengabdian untuk guru-guru SD di Kabupaten Bangkalan dapat disimpulkan berhasil sampai tahap pelatihan menganalisis data penelitian dengan menggunakan aplikasi SPSS dan dapat membaca hasil output dari hasil penggunaan aplikasi SPSS. Kata Kunci: Pelatihan, Aplikasi SPSS, Statistik